Charles Cowden Clarke and Mary Cowden Clarke correspondence - Clarke, Charles Cowden, 1787-1877.; Clarke, Mary Cowden, 1809-1898.
Letter of Charles C. Clarke and Mary Victoria Novello Cowden-Clarke.
Scholar and author.
Collection material in English.
Forms part of: Miscellaneous Manuscripts collection.
Keywords: Authors; Scholars